Competitiveness, labour market and protection of the right to work in the member countries of the Pacific Alliance - Julio-Rospigliosi Porretti, Vincenzo Domenico (2024)
The research determines the relationship between competitiveness, the labour market and the protection of the right to work at the constitutional level in the member countries of the Pacific Alliance, analysing for this (i) the evolution of the labour force of the members of the Pacific Alliance, (ii) the constitutional economic system and its competitiveness, (iii) the constitutional framework of the right to work and its related rights, as well as (iv) the situation of the labour market and business competitiveness in Chile, Colombia, Mexico and Peru. A qualitative approach is used at a descriptive, exploratory, and bibliographic level with emphasis on the theories put forward by Mortimore and Peres, Cardona-Arenas, Josling et al.; and Rojas and Terán. It is concluded that there is a direct relationship between competitiveness and job stability in the countries of the Pacific Alliance thanks to the regulatory frameworks of their laws for the protection of the individual rights of workers, despite the economic informality of their members and the socioeconomic inequities of its citizens. Data from the International Labour Organisation, United Nations Economic Commission for Latin America and the Caribbean, and the World Bank, from 2010 to 2023 were used, as well as bibliographic information.